1991
DOI: 10.1246/bcsj.64.1738
|View full text |Cite
|
Sign up to set email alerts
|

Formations of OH(X2II, A2Σ+) in the Reaction of NH(3Σ−) with NO in Incident Shock Waves

Abstract: Gaseous mixtures of HNCO and NO diluted in Ar were heated by incident shock waves to about 3500 K to investigate the bimolecular reaction of NH(3Σ−) with NO. Ultraviolet emissions from the excited NH(A3II) and OH(A2Σ+) were monitored to determine the rate constants for the ground-state reaction NH(3Σ−)+NO→N2+OH(X2II). The branching ratio defined as the rate constant for the formation of OH relative to that for the NH(3Σ−) decay was found to be 0.32±0.07 at the shock-wave temperature adopted. An intense spike o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
1

Year Published

1993
1993
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(13 citation statements)
references
References 11 publications
0
12
1
Order By: Relevance
“…Formation of isomers of HNCO could potentially enhance oxidation, similarly to what is observed for HCN (see section 3.4). The isomerization pathways for HNCO have been studied theoretically by several groups [108,179,180] who nd the pathway to HOCN to be energetically the most favorable. However, the overall barrier height is of the order of 90 kcal mol −1 , which is too high for the process to be signicant at the present temperatures.…”
Section: Modeling Hnco Oxidationmentioning
confidence: 99%
“…Formation of isomers of HNCO could potentially enhance oxidation, similarly to what is observed for HCN (see section 3.4). The isomerization pathways for HNCO have been studied theoretically by several groups [108,179,180] who nd the pathway to HOCN to be energetically the most favorable. However, the overall barrier height is of the order of 90 kcal mol −1 , which is too high for the process to be signicant at the present temperatures.…”
Section: Modeling Hnco Oxidationmentioning
confidence: 99%
“…Shock tube measurements of emissions from electronically excited OH and NH in HNCO--NO--Ar mixtures (Yokoyama et al 1991a(Yokoyama et al , 1991b were used with a complex model to infer a branching fraction of 0.32 ± 0.07 for the N2 channel at 3500 K. However, an analysis of ammonia flames (Vandooren et al 1991) suggested that the N2 channel is four to six times faster than the N20 channel at 2000 K. The more direct nature of the Mertens et al study suggests that their data are the most reliable. At low temperatures, the measurements of the overall rate coefficient exhibit quite good agreement, but there is controversy with respect to the products.…”
Section: Qrrk Treatmentsmentioning
confidence: 99%
“…There have been several measurements of the overall rate constants for NHϩNO, including room temperature studies, [1][2][3][4][5][6][9][10][11][12] shock tube, 7,8 and flame measurements. [13][14][15] The rate constant is found to have values in the range 3.8 -5.8ϫ10 Ϫ11 cm 3 /s at 300 K, increasing slowly with temperature.…”
Section: Introductionmentioning
confidence: 99%
“…Very recently Durant 9 has measured that HϩN 2 O is 84Ϯ40% of the products, while Lillich et al 11 have measured 15Ϯ5% OHϩN 2 , and Okada et al 12 have corrected Yamasaki's 100% OHϩN 2 down to 30Ϯ9%. Values for the OHϩN 2 fraction under shock tube conditions include 19Ϯ10% from Mertens et al 7 and 32Ϯ7% from Yokoyama et al 8 Another important issue concerning NHϩNO is partitioning of the exoergicity among the product degrees of freedom. Patel-Misra and Dagdigian 16 report that OH is only modestly excited, with (vϭ1)/(vϭ0)ϭ0.30Ϯ0.06, and an average rotational energy of 6 kcal/mol.…”
Section: Introductionmentioning
confidence: 99%